Provision of Basic Immunization for Toddlers during Covid-19 Pandemic in Mekarjaya Village Tangerang Regency - Siauta, Jenny Anna; Aulya, Yenny; Sukmawati, Dewi (International Health Sciences Journal, 2023)
Background: Immunization is important in health services to protect vulnerable individuals from PD3I. Immunization efforts make a significant contribution to increasing the Human Development Index related to one of its components, such as life expectancy, because it can avoid unwanted deaths, if not addressed immediately it will have an impact on increasing cases of Extraordinary Events and the spread of disease will accelerate. Especially during the the Covid-19 pandemic which caused restrictions on activities which certainly had an impact on participation in immunization visits at Posyandu. Objective: To determine factors that influence the obedience of mothers bringing their toddlers to get basic immunization during the Covid-19 pandemic in Mekarjaya Village, Tangerang Regency. Methodology: Using a cross sectional approach, a sample of 100 mothers who had toddlers. The research instrument was a questionnaire that had been tested valid and reliable, bivariate analysis had been done by the Chi Square test. Results: there is a significant relationship between knowledge, attitudes, motivation, family support and the role of cadres with mothers' compliance to bring toddlers to get basic immunization during the co-19 pandemic in Mekarjaya Village. Conclusion: Internal factors are the main factor for mother's compliance to bring their toddler to get immunization. It is hoped that mothers who have toddlers can increase their knowledge about the importance of immunization through various media and reliable sources.